Teachers’ Beliefs and Practices Regarding the Role of Executive Functions in Reading and Arithmetic - Rapoport, Shirley; Rubinsten, Orly; Katzir, Tami (Frontiers in Psychology, 2016)
The current study investigated early elementary school teachers’ beliefs and practices regarding the role of Executive Functions in reading and arithmetic. A new research questionnaire was developed and judged by professionals in the academia and the field. Reponses were obtained from 144 teachers from Israel. Factor analysis divided the questionnaire into three valid and reliable subscales, reflecting (1) beliefs regarding the contribution of executive functions to reading and arithmetic, (2) pedagogical practices, and (3) a connection between the cognitive mechanisms of reading and arithmetic. Findings indicate that teachers believe executive functions affect students’ performance in reading and arithmetic. These beliefs were also correlated with pedagogical practices. Additionally, special education teachers’ scored higher on the different subscales compared to general education teachers. These findings shed light on the way teachers perceive the cognitive foundations of reading and arithmetic and indicate to which extent these perceptions guide their teaching practices.